Intersections of exclusion: the institutional dynamics of combined gender and ethnic quota systems. (2nd April 2016) - Bird, Karen
Abstract : Despite growing interest in the politics of intersectionality, applications in the domain of electoral reform and political representation have been slow, both in scholarship and on the ground. This paper develops a new avenue of inquiry into this issue. Focusing on 17 countries that employ quotas/reservations for both women and ethnic minorities in elections to national parliament, I show that there are rarely representational gains for those located at the intersection of the two quota mechanisms. This is because quotas for women and minorities are rarely "nested." Rather they tend to operate independently, often through entirely separate contests to fill the parliamentary seats allotted to each group. Beyond developing a clearer specification of the rules and mechanical effects of dual quota systems, I apply a feminist institutionalist framework to gain greater insight into the informal dynamics that contribute to minority women's persistent under-representation in a variety of contexts. Finally, the paper sketches an agenda for transformative action and institutional reform to advance the political inclusion of ethnic minority women.